EPIDEMIOLOGICAL SITUATION THROUGH MEASLES IN PRYKARPATYA - Сенюта, Л. М.; Бойко, М. А.; Чурпіта, Є. Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Children’s illnesses department of Afterdiploma education faculty of Ivano-Frankovsk national medical university, the Ivano-Frankovsk regional sanitary and epidemiologic station. Children’s illnesses department of Afterdiploma education faculty of Ivano-Frankovsk national medical university, the Ivano-Frankovsk regional sanitary and epidemiologic station. Measles was known as the most dangerous children disease in beforevaccinal period, and it was named as “children plague”. At the beginning of the XXI century more than 40 millions of measles events had been registered every year, and about 1 million of children had died. Measles is a controlled infection, with the growth of disease each 4-5 years. The following peak of measles is necessary to expect in 2010. Least protected had been an age group from 18 to 38 years over the period of measles epidemic in 2005-2006 years, in which this disease was observed more frequent, was heavier, resulted development especially heavy complications and death. So, to prevent sharp growth of measles in our region it is worth to immunize those children, who remain not immunized without the powerful reason, and adults, especially up to 42 years old, to pay attention to quality of children nourishment in hospitals and educate parents. In case of registration of measles by clinical attributes, it is necessary to pay attention to laboratory confirmation of a clinical case.